NXF1 suppresses progression of endometrial cancer by interacting with the SRSF3 to regulate SP4 splicing - Nan Meng; Lingjun Li; Xueqin Yang; Hui Tang; Jizhong Wang; Songbai Zhang; Zongbao Xia; Jia Yao; Qi Zhang; Changrong Hu; Chunjie Su; Rui Duan (iScience, 2025)
Summary: Conventional treatments for advanced endometriosis often have limited efficacy due to chemotherapy resistance, recurrence, and metastasis. This study analyzed clinical specimens to investigate the role of NXF1 in endometrial cancer (ECa) progression. Mouse models and molecular biology assays were used to elucidate NXF1’s function and mechanisms in vitro and in vivo. Results showed NXF1 expression was negatively correlated with histological grade and poor patient prognosis. NXF1 inhibited ECa cell proliferation, colony formation, migration, and invasion in vitro, and suppressed tumor growth and metastasis in vivo. Mechanistically, NXF1 interferes with the binding of SRSF3 to exon 3 of SP4, preventing the formation of the “cancerous” long SP4 isoform (L-SP4) and promoting the “noncancerous” short SP4 isoform (S-SP4), which lacks the transactivation domain. In conclusion, NXF1 suppresses ECa tumorigenicity and progression through an SRSF3-mediated SP4 alternative splicing mechanism, and could serve as a novel prognostic biomarker for clinical intervention in ECa.